109 Multi-omic integration reveals intra-tumour heterogeneity and identifies disulfiram and copper as a synergistic therapy in paediatric ependymoma - Alina Pandele; Alison Whitby; Sandra Martinez-Jarquin; Chiara Bastiancich; Donald Macarthur; Ian Kamaly-Asl; David Barrett; Richard Grundy; Dong-Hyun Kim; Ruman Rahman (Neuro-Oncology, 2026)
Abstract Introduction Ependymoma (EPN) is the second most malignant paediatric brain tumour. The PF-A subgroup, associated with a hypoxic microenvironment, has a dismal survival rate of 50%, with clinical trials failing to demonstrate a significant survival advantage from chemotherapy to date. We present a multi-omic integration investigating whether spatially-distinct tumour microenvironments represent targetable metabolic niches in PF-A EPN. Methods Surgical sampling of spatially-distinct regions from eight PF-A patients was performed, with metabolites and RNA simultaneously extracted and analysed using LC-MS and RNA-seq. Integration of metabolites and RNA was performed using Metscape3 with functional assays evaluating proliferation and invasion in 2D and 3D patient-derived in-vitro cell models. LC-MS and qPCR were used to analyse post-treatment changes of our lead drug combination under hypoxia and normoxia. Clonogenic assays investigated radiosensitisation (±2 Gy) and in-vivo tolerability was evaluated in non-tumour-bearing mice (DSF/Cu2+ 200/4 mg/kg, i.p.). Results Multi-omic integration identified 124 dysregulated metabolic pathways, demonstrating heterogeneity within and across PF-A tumours. Based on the identified metabolically relevant genes, Disulfiram (Dsf) and Cu2+ were highlighted as potential therapeutic agents showing impaired metabolic viability and invasion in 2D and 3D models of PF-A EPN, with radiosensitising effects in 2D clonogenic assays and limited chemosensitivity observed in human cerebellar astrocytes. LC-MS revealed Dsf/Cu2+ disrupts mitochondrial fatty acid oxidation (normoxia) and TCA cycle intermediates (hypoxia). In vivo, DSF/Cu2+ showed no weight loss or overt toxicity in non-tumour-bearing mice. This combination also demonstrated efficacy in additional paediatric in-vitro models, suggesting pan-cancer potential. Conclusions This is the first instance where multi-omic data integration and intra-tumor heterogeneity have been investigated for paediatric EPN, revealing novel therapeutic targets in the context of gene-metabolite correlations.